Novel Finding of Lower Genital Tract Arteriovenous Malformation Leading to Massive Urethral Bleed - Paul Kim; James Kovacic; Ankur Dhar; Andrew R.H. Shepherd (Société Internationale d’Urologie Journal)
None.